2009
DOI: 10.1159/000229300
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of the Connexin 26 (GJB2) Mutation in Chinese Cochlear Implant Recipients

Abstract: Background: The GJB2 gene, mapping to chromosome 13q12, encodes a gap junction protein, connexin 26, and is responsible for certain forms of congenital deafness, such as DFNB1 and DFNA3. Mutations of this gene are responsible for about one half of severe autosomal recessive non-syndromic deafness. Methods: To determine whether GJB2 mutations are major causes of deafness in Chinese cochlear implant recipients, we enrolled 115 cochlear implant recipients for mutation screening. Results: The results showed that 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…In the present study, the results found that 16 cases of neonatal existed mitochondrial DNA12SrRNA m.1555A>G mutations and the carrying frequency was 1.6%, including one newborn carried a monoallelic mutation of SLC26A4 and 12S rRNA gene 1555A>G mutation. But it is lower than Chen et al reported as (0.7%) screened in 865 cases of neonatal [17]. Simultaneously, we also screened the other site that is associated with deafness caused by aminoglycosides, the results showed that three newborns carried the mitochondrial DNA C1494T mutation.…”
Section: Discussionmentioning
confidence: 64%
“…In the present study, the results found that 16 cases of neonatal existed mitochondrial DNA12SrRNA m.1555A>G mutations and the carrying frequency was 1.6%, including one newborn carried a monoallelic mutation of SLC26A4 and 12S rRNA gene 1555A>G mutation. But it is lower than Chen et al reported as (0.7%) screened in 865 cases of neonatal [17]. Simultaneously, we also screened the other site that is associated with deafness caused by aminoglycosides, the results showed that three newborns carried the mitochondrial DNA C1494T mutation.…”
Section: Discussionmentioning
confidence: 64%
“…In a study of a Chinese population, Dai et al (2007) reported that this genetic variant is significantly associated with deafness. Similarly, Chen et al (2009) found it to be more common among Chinese sufferers of nonsyndromic deafness. Padma et al (2009) investigated an Indian population, showing that the GJB2 235delC mutation is more prevalent among patients with hearing impairments than healthy controls.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have examined the association between the GJB2 235delC polymorphism and development of congenital deafness, but their results have been inconsistent Chen et al, 2009;Padma et al, 2009;Dzhemileva et al, 2010;Yang et al, 2013). In a study of a Chinese population, Dai et al (2007) reported that this genetic variant is significantly associated with deafness.…”
Section: Discussionmentioning
confidence: 99%
“…The difference among reported mutation frequencies of GJB2 gene was very large. The risk allele carrying frequency of GJB2 mutation ranged from 14.8% to 41% in China [7,8], 14.7% to 50% in Europe [9,10], and 3.01% to 26.3% in America [11,12]. Kimberling first raised the question as to why there was such a large difference among mutation frequencies in the same region or ethnic origin [13].…”
Section: Introductionmentioning
confidence: 99%